Upravljanje z divjadjo v Mestni občini Ljubljana - Miklavčič, Viktor (Gozdarski vestnik, 2010)
Specialty of the game management in Municipality of Ljubljana (below: MOL) is an intense influence of a large urban settlement and a large transition area from the urban into the rural environment. In the transition area, urban and agricultural or, respectively, non-hunting and hunting surfaces intertwine. This area represents a habitat of a lesser quality; however, it is still useful for the wildlife. Due to, among others, recreationists, it is hard or impossible to perform hunting. The problem of game management originates primarily in conflicts of interests of hunting and agriculture. Intentionally or not, the laity in form of strollers and recreationists also involves in this relation. The deer in MOL is, except in the urban environment, present practically everywhere, the wild boar is present in the forests and their vicinity where it has an undisturbed access from the rear, and the grey crow is present prevailingly in the lowland part of the MOL, regardless of the settlements.
Keywords: Ljubljana; Ljubljana City Municipality; Mestna občina Ljubljana; divjad; upravljanje z divjadjo; srnjad; divji prašič; siva vrana